2014
DOI: 10.1103/physreve.90.022901
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal transmission through a saturable nonlinear asymmetric dimer

Abstract: We investigate the nonreciprocal diodelike behavior of a dimer with an asymmetric on-site potential and a saturable nonlinearity. The dimer is coupled to linear side chains. The spectra of transmission and the rectifying factor are analytically obtained using a backward iteration of the set of discrete nonlinear Schrödinger equations used to model the wave propagation through the nonlinear dimer. We show that the windows of bistable behavior leading to a pronounced nonreciprocal diodelike transmission become w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…From Fig.6 we learn that for those parameter regimes, bulk of the transmission occurs for asymmetry ε v ≤ 0.2, and for saturation µ ≈ 2.5 ∼ 3.5. The cases of symmetry breaking by means of nonlinearity Fig.8 and Fig.10 suggest that it is possible to achieve higher transmission regimes for increased asymmetry levels which could be interesting to explore in the context of a diode-like transmission because, as discussed earlier in this paper and other studies [17,18,33,34], higher asymmetry renders a better diode-like action but with reduced overall transmission.…”
Section: Threefold Symmetry Breakingmentioning
confidence: 63%
“…From Fig.6 we learn that for those parameter regimes, bulk of the transmission occurs for asymmetry ε v ≤ 0.2, and for saturation µ ≈ 2.5 ∼ 3.5. The cases of symmetry breaking by means of nonlinearity Fig.8 and Fig.10 suggest that it is possible to achieve higher transmission regimes for increased asymmetry levels which could be interesting to explore in the context of a diode-like transmission because, as discussed earlier in this paper and other studies [17,18,33,34], higher asymmetry renders a better diode-like action but with reduced overall transmission.…”
Section: Threefold Symmetry Breakingmentioning
confidence: 63%
“…Finally, we should note that after submission of this manuscript, we were notified of a related work in [28]. While the models analyzed in these works are fairly similar, distinctive features of the present work are (a) that we explored systematically the stability of the extended waves and we studied the outcomes of their dynamical instabilities; and (b) we also considered the effect of the incidence of a Gaussian wave packet.…”
Section: Discussionmentioning
confidence: 91%
“…The authors in Ref. [45] investigated in detail the nonreciprocal diode-like behavior of an asymmetric dimer with saturable nonlinearity. It was found that the transmission band becomes wider and displaces to the higher input field intensities as the saturation coefficient increases.…”
Section: Introductionmentioning
confidence: 99%